Association between sex hormone levels and abnormal metabolism in a population of elderly Chinese men. (March 2013) - Gong, Yanping; Xiao, Haiying; Bai, Jie; Li, Chunlin; Wen, Xinyu; Cheng, Xiaoling; Fu, Shuhong; Lu, Yanhui; Li, Xiaoxia; Shao, Yinghong; Li, Yanyan; Jin, Mengmeng; et al.
Abstract Objective: Low testosterone levels may be a signal of poor health. This study aimed to investigate the effects of age and abnormal metabolism on sex hormones in Chinese male. Methods: Three hundred and thirty-seven elder men were enrolled into this single-center, cross-sectional study, and their sex hormone levels and metabolic parameters were assessed. Results: Serum follicle-stimulating hormone (FSH), luteinizing hormone (LH) and sex-hormone-binding globulin (SHBG) concentrations increased with age, while free testosterone index (FTI), testosterone secretion index (TSI), estradiol (E2)/SHBG and progestin (PROG) decreased. Abnormal metabolisms were related to androgen indices (TT, FT, BT, FTI, TSI, T/E2), SHBG and E2/SHBG even after adjusting by age and macrovascular disease. Obesity and overweight, hyperglycemia and dyslipidemia were the most important abnormal metabolism that related to decreased androgen indices. Including SHBG in the stepwise regression increased the explanation effect of TT and BT by 32.7% and 28.5%, respectively, and all metabolic indices were excluded. Abnormal metabolism indies (BMI and PBG) were correlated to the decrease in SHBG levels, while age and LH was positively correlated to SHBG levels. Conclusions: Age and abnormal metabolism were independently important factors associated with the sex hormone levels in elderly Chinese men, which were all mediated by SHBG.